Synthesis and Evaluation of a New Type of Small Molecule Epigenetic Modulator Containing Imidazo[1,2-b][1,2,4]triazole Motif - Wu, Fan; Zhang, Jing; Shang, Erchang; Zhang, Junzhi; Li, Xiang; Zhu, Bing; Lei, Xiaoguang (Frontiers in Chemistry, 2018)
Epigenetic modifications such as DNA methylation are important for many cellular processes, such as cell differentiation and cell death. The disorder of epigenetic state is closely related to human diseases, especially cancers. DNA methylation is a well-characterized epigenetic modification which is related to gene silencing and is considered as a repressive epigenetic mark. DNA methylation caused gene repression can be derepressed by chemical agents. Small molecules targeting DNA methyltransferases, histone deacetylases, and other regulatory factors can activate genes silenced by DNA methylation. However, more and more studies have shown that histone deacetylation is not the only downstream event of DNA methylation. Some additional, unknown mechanisms that promote DNA methylation-mediated gene silencing may exist. Recently, through high-throughput screening using a 308,251-member chemical library to identify potent small molecules that derepress an EGFP reporter gene silenced by DNA methylation, we identified seven hit compounds that did not directly target bulk DNA methylation or histone acetylation. Three of them (LX-3, LX-4, LX-5) were proven to selectively activate the p38 MAPK pathway in multiple cell types. In order to identify the exact cellular targets of these compounds, we turn to work on the SAR study of LX-3 by constructing a structurally diverse chemical library based on the imidazo[1,2-b][1,2,4]triazole core structure via diversity-oriented synthesis. Our work provides a general approach to efficiently access diverse heterocyclic molecules with interesting epigenetic modulation activities.